CFD Analysis of Indoor Chlorine Gas Dispersion Storage: Temperatures, Wind Velocities and Ventilation Effects Studies - M Safakar; S Syafiie; R Yunus (ASEAN Journal of Chemical Engineering, 2016)
The Chemical products factories encounter inherent environmental risks in the process. The indoor release of hazardous chemical gases that are heavier than the air is nowadays a special subject for scrutiny because the dense clouds of the gas have a tendency to insist on the ground level or near the human breath level, causing fatal injuries or other potential health threats to human beings. In this study, a computational fluid dynamics (CFD) code FLUENT was employed in order to model the accidental indoor dispersion of a dense gas (chlorine) from a small undetected leak in an indoor industrial environment. Furthermore, the effects of different temperatures, wind velocities and ventilation on diffusion of chlorine are investigated in this paper. Results of the simulations represented that the chlorine gas dispersion would behave like the liquid and currents on the floor. It was also found that the chlorine concentration above the ground level increased slowly. Showing the effects of various temperatures and wind on spreading the dense gas will help to better identify the potential risks. In this research, the effects of the environmental situations with the release and spread of chlorine in the indoor space were meticulously investigated.